Patient-Reported Outcomes: a Compass Through Inflammatory Bowel Disease Journey - Ana-Maria BAICEANU; Teodora Iulia SPATARU; Marina COZMA; Remus POPESCU; Lucian NEGREANU (Modern Medicine)
Inflammatory bowel disease (IBD) are chronic inflammatory conditions which have a major impact on the patients’ quality of life. Patient reported outcomes (PROs) help empower the patients giving them a voice in their treatment decision and improving communication between patients and doctors. PROs represent a foundation for a tailored approach of IBD monitoring and treatment and are very important in both research and routine clinical management. Improved PROs tools will facilitate their use in daily practice, in turn improving the delivery of value-based healthcare and, in the long term, good clinical care of the patients. This review is focused on the main principles regarding PROs role and their importance in IBD care.